حوكمة الجامعات:مفهومها وأهدافها ومبادئها - شيماء خالد شعبان محمد (المجلة المصرية لعلوم المعلومات, 2024)
تهدف هذه الدراسة إلى التعرف على مفهوم الحوكمة وأهميتها في الجامعات، وأسباب ظهورها ومبادئها، ومتطلبات تطبيقها في الجامعات. وقد اعتمدت الدراسة على المنهج الوصفي، وتوصلت الدراسة إلى أن الحوكمة هي النظام والأسلوب الذي يبنى من خلاله اتجاهات إدارية حديثة، من خلال مجموعة من القواعد والقوانين والمعايير والممارسات التي يتم من خلالها إدارة المؤسسات، والتحكم والرقابة الفعاله في أعمالها، وتنظيم العلاقات بين الأطراف الأساسية التي تؤثر في العمل . كما تشمل تحديد المسئول والمسئولية في إطار من الشفافية والمساءلة.This study aims to identify the concept of governance and its importance in universities, the reasons for its emergence and its principles, and the requirements for its application in universities.The study relied on the descriptive approach, and the study concluded that governance is the system and method through which modern administrative trends are built, through a set of rules, laws, standards and practices through which institutions are managed, effective control and oversight of their work, and organization of relationships between the main parties that Affect work. It also includes determining who is responsible and accountable within a framework of transparency and accountability..